PENGARUH KEMAMPUAN MENGAJAR GURU DAN KEMANDIRIAN BELAJAR TERHADAP PRESTASI BELAJAR IPS SISWA KELAS VII SMP NEGERI 34 PEKANBARU - Deswita. S Deswita. S; Sumarno Sumarno; Hendripides Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to know the influence of teaching ability of teachers and independence learning on the social learning achievement of seven grade student at pekanbaru 34 junior high school. The population in this study is 160 students from class VII 4 – VII 7. The samples in this study were taken by the Slovin method of up to 62 students, using a proporsional random sampling technique. Data collection techniques by using documentation and questionnaires. Data analysis using descriptive analysis and multiple linear regression. Descriptive, teacher’s teaching abilities is included in the medium category, independence learning included in the good category, and learning achievement is included in the enough category. The teaching ability of teacher and independence learning has a significant impact on learning achievement with the regression equation Y= 4,291+0,566X1+0,219X2 and contribute to the learning achievement by 54,1%Key Words: Teaching Ability of Teachers, Independence Learning, and Learning Achievement.